Peningkatan Keterampilan Guru PAUD Melalui Pemanfaatan Wordwall Pada Literasi Digital Sebagai Upaya Pengoptimalan Proses Pembelajaran - Harianja, Sri Indriani; Hasni, Uswatul; Amanda, Rizki Surya; Utami, Winda Sherly; Rosyadi, Akhmad Fikri (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Educators in Early Childhood Education Institutions must follow the development of the era which is experiencing drastic changes every day. The existence of these changes is a demand that is expected by society for teachers to update their knowledge and understanding of the teaching and learning process that is fun and motivates their students. One alternative that fosters these things is through the use of digital applications. The use of these digital applications can be implied through smartphones and laptops. One of the demands of the development of the era makes teachers literate in the digital world. Wordwall is one of the alternative digital applications that can be used by teachers to help digital literacy, especially for early childhood. Simply put, this digital media provides a varied learning process by producing images, sounds, letters, colors, and others so that children's curiosity can be increased through wordwall learning media. This application is very easy to use by teachers so that there is no longer a term of technological failure for educators. The purpose of this community service activity is to provide assistance to PAUD teachers to improve skills and knowledge in utilizing digital media facilities to create interesting and not boring learning for early childhood, especially for early childhood literacy. The stages in this community service are the activity planning stage, preparing the design, implementing activities, and the activity evaluation stage. The results of this community service activity are that there is an increase in the skills and knowledge of teachers regarding wordwall learning media for early childhood literacy. Thus, it can be said that mentoring activities have a positive contribution to teachers in increasing their insight into wordwall-based learning media to support learning activities in PAUD Institutions. Keywords: wordwall, teacher skills